Strategi Guru dalam Menyesuaikan Pengurangan Materi pada Kurikulum Merdeka di SDN Sungai Miai 10 - Arina Mawaddah; Aslamiah Aslamiah; Diani Ayu Pratiwi; Hersa Aulia Wati; Siti Rabbiatul Hasanah; Siti Zahra (CV. ITTC INDONESIA, 2025)
The Independent Curriculum (Curriculum Merdeka) brings significant changes to the learning structure in elementary schools, including the simplification and reduction of material in several subjects. At SDN Sungai Miai 10, these adjustments pose challenges for teachers, such as limited training, student readiness, and learning time management. This study aims to analyze teachers' strategies in adapting to the reduced material in the Independent Curriculum, identify the obstacles encountered, and evaluate the effectiveness of these strategies. The research used a qualitative approach with a case study method through in-depth interviews with the principal and class teachers directly involved in the curriculum's implementation. Data were analyzed thematically to identify patterns in the strategies used. Findings indicate that teachers addressed the reduced material by reinserting removed topics into relevant lessons, implementing project-based learning, a thematic approach, and formative assessment. These strategies increase student engagement, maintain conceptual understanding, and tailor learning to students' needs. However, the success of these strategies is greatly influenced by teacher readiness and ongoing training support. This study emphasizes the importance of supporting facilities, flexible teaching modules, and regular evaluation to ensure the effective implementation of the Independent Curriculum in elementary schools.